Responsiveness of Inhaled Corticosteroid Treatment in Children with Asthma: The Role of rs242941 Polymorphism of CRHR1 Gene - Hanh Nguyen-Thi-Bich; Thuy Nguyen-Thi-Dieu; Le Nguyen-Ngoc-Quynh; Huong Le-Thi-Minh; Sy Duong-Quy (Pulmonary Therapy, 2022)
Abstract Introduction Inhaled corticosteroid (ICS) is the most widely used and effective treatment of asthma. However, some patients do not respond to ICS, which might be due to various genetic factors. Hence, understanding the genetic factors involved in the ICS response could help physicians to individualize their treatment decision and action plans for given patients. This study aimed to analyze the characteristics of corticotropin-releasing hormone receptor 1 (CRHR1) genotypes in children with asthma and the correlation between rs242941 polymorphism of CRHR1 gene and ICS responsiveness. Methods This prospective study included children with uncontrolled asthma, assessing their eosinophil count, IgE concentration, lung function, and fractional concentration of nitric oxide in exhaled breath (FENO) and performing CRHR1 polymorphism sequencing. The level of asthma control was assessed by asthma control test (ACT); the responsiveness of asthma treatment with ICS was evaluated by measuring the change of ACT and forced expiratory volume in 1 s (FEV1) after treatment versus at inclusion. Results In total, 107 patients were analyzed for CRHR1 at rs242941. Among these, 86 (80.3%) had homozygous wild-type GG, 20 (18.7%) had heterozygous GT genotypes, and 1 (1.0%) had a homozygous variant for TT. Children with personal and family history of atopy were more likely to have GT and TT genotypes. The severity of asthma was similar between children with asthma in the three groups of GG, GT, and TT genotypes of CRHR1 at rs242941. FENO level, total IgE concentration, and eosinophilic count in children with asthma were not significantly different between GG and GT genotypes. The patient with a TT homozygous variant genotype had a higher level of FENO. There was no correlation between CRHR1 polymorphism at rs242941 and asthma control evaluated by asthma control test and lung function parameters. Conclusion TT genotype of rs242941 in the CRHR1 gene is not frequent. Clinical and functional characteristics of children with asthma with rs242941 polymorphism of CRHR1 gene remain homogeneously similar. There is no correlation between rs242941 polymorphism and ACT or FEV1.